Tracing the Coloniality of Queer and Trans Migrations: Resituating Heterocisnormative Violence in the Global South and Encounters with Migrant Visa Ineligibility to Canada - Edward Ou Jin Lee (Refuge)
Most of the scholarship on queer and trans migrants focuses on the refugee experience post-migration to Canada. In contrast, this article draws from a doctoral study that included participant interviews and policy/media textual analysis to map out the historical, geopolitical, social, and economic dimensions that shape homophobic and transphobic violence across the globe, as well as queer and trans migrations from the Global South to Canada. These realities are analyzed through the lens of coloniality and on the scale of empire to historicize how queer and trans migrant lives are shaped by forgotten histories of colonial violence. This study suggests that the hyper-visibility of Canada’s “generous” treatment of queer and trans refugees obscures how its border regime blocks people from the Global South from entry.